Mikroenkapsulacja probiotyków - Kołodziej, Maciej; Łukasik, Jan; Szajewska, Hanna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Probiotics are live microorganisms that, when administered in adequate amounts, confer a health benefit on the host. External factors such as temperature, moisture, oxygen, and degradation in the gastrointestinal tract due to gastrointestinal fluids and enzymes may influence the viability of probiotic microorganisms. This article summarizes data relevant to practicing physicians on microencapsulation (a process in which active substances are surrounded by a coating to provide extremely small capsules) as a means of enhancing probiotic resistance to environmental factors.